Impact of Preservation Using Moringa (Moringa oleifera L.) Leaf Juice on Chicken (Gallus gallus domesticus) Egg White Index - Putra, Sukarman Hadi Jaya (Proceeding International Conference on Religion, Science and Education, 2022)
This study aimed to determine the consistency of the egg white index of native chickens (Gallus gallusdo domesticus) after soaking eggs in Moringa leaf juice. It aims to extend the shelf life of eggs. Egg white consistency is one way to measure the quality level of eggs that have been stored for a certain time. The egg quality variables measured were egg white diameter and egg white height, so the egg white index was obtained. The higher the egg white index, the better the egg quality. The material used is a solution of Moringa leaf juice to soak the eggs for 24 hours to maintain the consistency of the egg white index. Soaking is to maintain the state of the inside of the egg. The ingredients in Moringa leaves are used to wrap eggs to avoid the invasion of harmful microorganisms. In this study, a completely randomized design (CRD) was used. Moringa leaf juice had 4 concentrations, namely 0%, 15%, 30%, and 45%. Each concentration treatment was repeated 5 times. The number of eggs required is 1000 eggs, of which a sample of 420 eggs is used for processing. Eggs used in good condition are brown eggs, clean, intact, not cracked, smooth texture, and oval shape. The randomization method used random sampling in the form of a lottery system. Each of the 420 eggs is labeled. Randomly selected eggs were divided into 4 treatment groups. The soaking process is for 24 hours, then the eggs are dried in the sun and then stored in a room with a temperature between 28-30 degrees Celsius. Storage time and the internal quality of eggs will be tested for 21 days. This is done to determine the level of egg resistance accurately because the embryonic development period of the egg is 21 days. Every day at 08.00 WITA to measure egg parameters. The egg quality parameter analyzed was Egg White Index. All measurement data were analyzed by analysis of variance (ANOVA). If the results of the analysis have an effect, then the Tukey test is continued with 95% confidence (?> 0.05). The data analyzed showed that eggs soaked in a solution of Moringa leaf juice had a higher and more stable egg white index than eggs that were not soaked in a solution of Moringa leaf juice. The optimal concentration to maintain the egg white index is 45%. Therefore, soaking eggs with Moringa leaves helps maintain the consistency of the egg white index.